2013
DOI: 10.7150/jca.5112
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment Contribution to Development, Growth, Invasion and Metastasis of Head and Neck Squamous Cell Carcinomas

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a complex tissue that contains tumor cells and the surrounding stroma, which is populated by different types of mesenchymal cells and the extracellular matrix (ECM). Collectively, they are referred to as the tumor microenvironment (TME). Recent studies have shown that TME has a more profound influence on the growth and metastasis of HNSCC than was previously appreciated. Because carcinoma-associated fibroblasts (CAFs) are frequently observed in the stroma of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
0
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(233 citation statements)
references
References 173 publications
1
200
0
18
Order By: Relevance
“…Recently, increasingly more studies have shown that tumor growth, development, invasion and metastasis depend on the tumor microenvironment and tumor metabolism (3). Water molecules play a significant role in the progression of malignant epithelial tumors, an understanding of which is thus important in anticancer treatment strategy (4).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasingly more studies have shown that tumor growth, development, invasion and metastasis depend on the tumor microenvironment and tumor metabolism (3). Water molecules play a significant role in the progression of malignant epithelial tumors, an understanding of which is thus important in anticancer treatment strategy (4).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of type IV collagen is associated with increased levels of MMP-9 in HNSCC (23). In HNSCC increased levels of MMP-9 are also associated with increased lymphonodal metastasis (24).…”
Section: Effect Of Selective Small Molecule Inhibitors On Mmp-9 and Vmentioning
confidence: 93%
“…They produce enzymes that release angiogenic factors sequestered in the extracellular matrix and stimulate adjacent normal tissues to make enzymes such as stromelysin and collagenase that can be activated to promote angiogenesis. 34 …”
Section: Effect Of Tumour Cells On Angiogenesismentioning
confidence: 99%